Profile of gantenerumab and its potential in the treatment of Alzheimer’s disease [Corrigendum] - Novakovic D; Feligioni M; Scaccianoce S; Caruso A; Piccinin S; Schepisi C; Errico F; Mercuri NB; Nicoletti F; Nisticò R (Dove Medical Press, 2014)
Novakovic D, Feligioni M, Scaccianoce S, et al. Drug Des Devel Ther. 2013;7:1359–1364.On page 1362, left hand column, last sentence under Functional studies:The effects of gantenerumab on cognitive assessment in the Morris water maze test were inconclusive, as both wild-type and transgenic AD mice injected with vehicle displayed impairment of learning, which might be ascribed to stress conditions caused by weekly intracerebroventricular injections. Importantly, neurological or motor impairments were not detected even after 5 months of treatment.24Should read as:The effects of gantenerumab on cognitive assessment in the Morris water maze test were inconclusive, as both wild-type and transgenic AD mice injected with vehicle displayed impairment of learning, which might be ascribed to stress conditions caused by weekly intravenous injections. Importantly, neurological or motor impairments were not detected even after 5 months of treatment.24Read the original article